(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
In this essay, the result of his participation in an event on myth and the gaze in the city of Ljubljana, in 2014, the French-Uruguayan playwright Sergio Blanco (1971-) explores metaphors present in the myths of Narcissus and Medusa to analyze the artist’s gaze, because, according to him, such myths have characteristics that resemble the process of artistic creation. Among these characteristics, Blanco lists three fundamental aspects, namely: the game between the self and the other, the power to transform and the search for immortality. Thus, it is through them that the artist transforms reality and marks his name in the history of the world through another reality that did not exist before.